Histopathology confirms white-nose syndrome in bats in Europe - Pikula, Jiri; Bandouchova, Hana; Novotny, Ladislav; Meteyer, Carol U; Zukal, Jan; Irwin, Nancy R; Zima, Jan; Martínková, Natália (Journal of wildlife diseases, 2012)
White-nose syndrome, associated with the fungal skin infection geomycosis, caused regional population collapse in bats in North America. Our results, based on histopathology, show the presence of white-nose syndrome in Europe. Dermatohistopathology on two bats (Myotis myotis) found dead in March 2010 with geomycosis in the Czech Republic had characteristics resembling Geomyces destructans infection in bats confirmed with white-nose syndrome in US hibernacula. In addition, a live M. myotis, biopsied for histopathology during hibernation in April 2011, had typical fungal infection with cupping erosion and invasion of muzzle skin diagnostic for white-nose syndrome and conidiospores identical to G. destructans that were genetically confirmed as G. destructans.
Keywords: Ascomycota; Evropa; Europe; dermatomykózy; hibernace; Male; Disease Outbreaks; Animals; Dermatomycoses; mužské pohlaví; ženské pohlaví; Female; Chiroptera; zvířata; Hibernation; epidemický výskyt choroby